2018
DOI: 10.1111/andr.12474
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine and psychological aspects of sexual dysfunction in Klinefelter patients

Abstract: Klinefelter syndrome is a frequent cause of hypogonadism, but despite hundreds of publications on different aspects of Klinefelter syndrome, only a few studies dealt with sexual dysfunction. In particular, testosterone is critical for various aspects of sexual response, but its role on sexuality in Klinefelter syndrome patients is debatable and no studies have evaluated the efficacy of testosterone treatment on sexual dysfunction in these subjects. Furthermore, the impact of psychological and relational aspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Interestingly, when patients experienced decline in sexual function and had PE or ED at the same time, the difference in emotion and life quality/satisfaction measurements increased. According to previous studies, some possible mechanisms are as follows: (1) Great sex brings about great self‐esteem, improving self‐worth; (2) more feel‐good hormones are secreted in the brains of sexually active men, resulting in better life experience and emotions (Ferlin et al, 2018); and (3) sex is a good way to improve marital relationships. We suppose that sexual dysfunction and decline in sexuality could contribute to negative moods and poor quality of life or make it worse.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, when patients experienced decline in sexual function and had PE or ED at the same time, the difference in emotion and life quality/satisfaction measurements increased. According to previous studies, some possible mechanisms are as follows: (1) Great sex brings about great self‐esteem, improving self‐worth; (2) more feel‐good hormones are secreted in the brains of sexually active men, resulting in better life experience and emotions (Ferlin et al, 2018); and (3) sex is a good way to improve marital relationships. We suppose that sexual dysfunction and decline in sexuality could contribute to negative moods and poor quality of life or make it worse.…”
Section: Discussionmentioning
confidence: 99%
“…Psychosexual development is often delayed and sexual problems might be more frequent in KS 164 . Most patients identify as male, but gender incongruence in KS has been reported in some studies 72,165‐173 …”
Section: Clinical Pictures Diagnostic Steps and Therapymentioning
confidence: 99%
“…[159][160][161][162][163] Psychosexual development is often delayed and sexual problems might be more frequent in KS. 164 Most patients identify as male, but gender incongruence in KS has been reported in some studies. 72,[165][166][167][168][169][170][171][172][173] Values Attention to eventual psychological, sexual, psychiatric as well as gender incongruence aspects is suggested (Table 2).…”
Section: Evidencementioning
confidence: 99%
“…On the other hand, other data showed that ED in KS is also linked to psychological disturbances, while erectile function seems to be less related to T levels and hypogonadism. Moreover, T replacement therapy is not able to improve erections [ 25 ]. Therefore, the exact role of T in the sexuality of KS patients is still debated.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, psychological and cognitive aspects are quite typical in KS and have been extensively investigated [ 24 ]. In particular, some psychological disturbances have been linked to ED in KS, while the role of T levels and hypogonadism in sexual function of subjects with KS is not fully elucidated [ 25 ]. Moreover, sexual function in KS has not been studied in depth, and only a few studies have investigated the different roles of hormonal, neuropsychological, cognitive, and relational disturbances.…”
Section: Introductionmentioning
confidence: 99%